Learning from experience: a theoretical framework for the work activity analysis and safe design - Cecilia De la Garza; Elie Fadier (Activités)
Many studies were conducted in GIPC-PROSPER, a French multi-field project concerning “Integration of Prevention into Design process” (Fadier, Neboit, & Ciccotelli, 2003). One of the main objective consisted in developing a theoretical framework and methodological rules allowing the best to be taken into account into design process the conditions of use equipment work. The main result was the development of new concepts (boundary Activities Tolerated during Use and Boundary Conditions Tolerated by Use). Results showed that the analysis of the work activity could be a real tool for a better design. Thus, the return-of-experience at the end of the analysis of work activities can involve different type of designers and owners. The capacity of these analyses to anticipate future operation is significant, even if the way in which they can be integrated into the design is still lacking. However, the ultimate goal is to integrate them in the specifications that need to be satisfied.